BIVARIATE DEPENDENCY FOR THE VEHICLE ROUTING PROBLEM WITH TIME WINDOWS - Pérez-Rodríguez, Ricardo; Hernández-Aguirre, Arturo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
The main purpose of the vehicle routing problem (VRP) is to deliver a set of customers with known demands on minimum travel routes starting and terminating at the same depot. The vehicle routing problem with time windows (VRPTW) requires the delivery made in a specific time window for every customer and returning to the depot before a due time. Contrary to current research, an estimation of distribution algorithm-based approach is proposed and developed to solve the problem and implement the solution. The approach mentioned makes use of a probability model based on the Pearson's correlation coefficient to describe the distribution of the solution space. Different and diverse instances served as input and test parameters in order to show that the estimation of any relationship and/or interaction between vertices on the sequence of the VRPTW solution can be improved. A better position for each vertex on the sequence can be estimated through a probability model using the Pearson's correlation coefficient.